Canadian Nurses' Perspectives on Prostate Cancer Support Groups: A Survey Study. Issue 3 (May 2016) - Yu Ko, Wellam F.; Oliffe, John L.; Han, Christina S.; Garrett, Bernie; Henwood, Tim; Tuckett, Anthony G.; Sohrevardi, Armin
Abstract : Background: Prostate cancer support groups (PCSGs) are community-based organizations that offer information and psychosocial support to men who experience prostate cancer and their families. Nurses are well positioned to refer men to a range of psychosocial resources to help them adjust to prostate cancer; however, little is known about nurses' perspectives on PCSGs. Objective: The aim of this study was to describe nurses' views about PCSGs as a means to making recommendations for advancing the effectiveness of PCSGs. Methods: A convenience sample of 101 Canadian nurses completed a 43-item Likert-scale questionnaire with the additional option of providing comments in response to an open-ended question. Univariate descriptive statistics and content analysis were used to analyze the quantitative and qualitative data, respectively. Results: Participants held positive views about the roles and potential impact of PCSGs. Participants strongly endorsed the benefits of support groups in disseminating information and providing support to help decrease patient anxiety. Online support groups were endorsed as a practical alternative for men who are reluctant to participate in face-to-face groups. Conclusions: Findings suggest that nurses support the value of Canadian face-to-face and online PCSGs. This is important, given that nurses can help connect individual patients to community-based sources providing psychosocial support. Implications for Practice: Many men benefit from participating in PCSGs. Aside from positively endorsing the work of PCSGs, nurses are important partners for raising awareness of these groups among potential attendees and can directly contribute to information sharing in face-to-face and online PCSGs.